Stochastic Modeling of Structural Fatigue Damage in High Strength Steel Structures (Fracture and Structural Integrity, 2024)
The paper proposes a parallel extension of the Direct Optimized Probability Computation Method. This method can be used as an alternative to Monte Carlo – based approaches for problems of structural reliability. It does not depend on any kind of randomly generated numbers, but it requires a much higher number of computations thus it can benefit from its parallelization. The proposed parallel Direct Optimized Probability Computation method is developed and studied on the problem of fatigue damage prediction. Description of the parallel algorithm is provided, and the functionality of the method is shown in an example case. The results are also compared to the results of the more common Monte Carlo – based approach.
Keywords: Probability of Failure; Fatigue; High Strength Steel; Direct Optimized Probability Computation Method; Parallel Processing